IMPLEMENTATION OF AUDIO LINGUAL METHOD IN TEACHING ENGLISH VOCABULARY AT AKADEMIKA KINDERGARTEN BEKASI - Rahman, Devini Aulya; Hidayati, Dini; Wardana, Heri (Pedagogi: Jurnal Ilmiah Pendidikan, 2024)
The objectives of this research are: 1) To describe the implementation of audio-lingual method in teaching English vocabulary at Akademika Kindergarten Bekasi. 2) To describe the evaluation of audio-lingual method in teaching English vocabulary at Akademika Kindergarten Bekasi. This research method is a qualitative method. Data collection techniques used observation, interview, and documentation. The subjects of this research are class B teachers and 14 class B students. The validity instrument for this research are source triangulation and technical triangulation. The findings of this research are: 1) The implementation of audio-lingual method in teaching English vocabulary consists of; a) The goal of English teaching and learning is that teachers use this method to familiarize and broaden children's knowledge in vocabulary and simple English conversation b) Procedures of teaching English vocabulary categorized in 3 activities; opening activities, core activities, and closing activities. c) Techniques of audio-lingual method used are repetition drill, question and answer drill, and dialogue memorization d) Advantages and disadvantages of audio-lingual method, the advantages are saving time and quite helpful in improving students' English vocabulary skills because students can already repeat and memorize some vocabulary and the disadvantages are that students feel bored and less focused on the lesson. 2) The evaluation of audio-lingual method used are; a) Review b) Questions and Answers c) Quiz.